Bradycardia secondary to autonomic involvement by small cell lung cancer - Sharma, Vishnu; Bagrodia, Vansh; Gupta, Shraddha (International Journal of Research in Medical Sciences, 2024)
We present a case of a male in late 50s with Small Cell Lung Cancer (SCLC) who came with near-fainting episodes and was found to have unexplained bradycardia despite thorough evaluation ruling out common causes. Autonomic testing revealed involvement of both sympathetic and parasympathetic nervous systems, likely due to tumor encasement of cardiac nerve supply. This case illustrates an unusual etiology for bradycardia in SCLC cancer patients, developing from secondary effects due to physical extension of tumor.